(untitled) (Research, Society and Development, 2019)
Community-based tourism corresponds to an economic modality whose premise is to develop local tourism, as well as the valorization of traditional culture and the preservation of biodiversity, providing the receiving communities with the generation of benefits. In this context, this work aimed to identify, through observation, interviews with owners of local enterprises and questionnaires applied to tourists who visited the region, the key indicators, based on sustainability pillars, that could serve as auxiliary tools for the development of the Tourism in the region of Serra dos Alves, Itabira (MG). Thus, the key indicators were subdivided into socio-cultural, economic, tourism and environmental dimensions to evaluate tourism development in the Serra dos Alves region. It is noteworthy that in the environment dimension it is necessary the intervention of the public agencies for the adequacy of the water supply of the community and elimination of the sources of pollution of the tourist attractions. For the economic and tourist activity dimensions, the positive results are the generation of income and local employment, as well as the great general impression of the place perceived by the tourists, which contribute to the socioeconomic development. It should be emphasized that the use of indicators to evaluate the development of community-based tourism activity is relevant to the design of planning strategies that lead to local development practices on a sustainable basis, contributing positively to the relationship of interdependence between the Tourism and the environment.